Determinação de risco (toxicidade/alergenicidade) de proteínas do látex de Calotropis procera como insumo terapêutico - Almeida, Marina Gabrielle Guimarães de (2025)
Calotropis procera is a laticifer plant from the Apocynaceae family, native to India, widely used in traditional medicine, where several pharmacological properties of the latex solubleproteins (LP) of this species are being reported, such as anti-inflammatory, analgesic, antitumor, anticancer, anti-hyperglycemic and antioxidant activities, among others. Recently LP was used in the development of a rennet for cheese production, and in the development of a polyvinyl alcohol (PVA)-based biomembrane for wound healing, tested in an animal model. Despite the studies conducted regarding the potential for application of LP as phytotherapeutic and the already reported safety of these proteins, the present study aims to improve the evaluation of the toxicological and allergenic properties, as well as to present a better understanding of the safety of use of biotechnological inputs produced from C. procera LP. To this end, oral toxicity tests were performed in Swiss mice for 28 days on 3 different doses of LP (1000, 500 and 250 mg/mL), then biochemical, histological, and hematological parameters were analyzed for changes that could indicate toxicity. To analyze the stability of LP, in vitro digestibility assays were executed in simulated gastric and intestinal fluids in sequential and non-sequential manner. To investigate the allergenicity of latex proteins, a patch test was performed in humans with PVA-based biomembranes (BioMem CpLP). At the three doses tested for toxicity, no change was seen within the parameters analyzed that could indicate LP as an orally toxic substance. In the allergenicity test, 52 volunteers participated in the study, where 12% of the volunteers had a mild allergic reaction in the first phase and 5% of the volunteers who completed the first phase had mild allergic reaction, showing that PL is safe for therapeutic use. This study suggests that C. procera latex proteins are safe for use for their therapeutic potential in these conditions.